Professional Bereavement Photography in the Setting of Perinatal Loss: A Qualitative Analysis - Faustine D. Ramirez MD; Jori F. Bogetz MD; Megan Kufeld BS; Lynn M. Yee MD, MPH (SAGE Publishing, 2019)
Perinatal loss, including fetal and infant death, is a devastating experience for parents, resulting in long-term adverse physical and psychosocial outcomes. However, little is known about what services might best support grieving parents. We aimed to understand the role of professional bereavement photography in assisting the grieving process of parents who have lost a fetus or infant, by examining the perspectives of bereaved parents, professional photographers, and health care professionals. Twenty semistructured interviews were conducted, and interview transcripts were analyzed using modified grounded theory. Twenty-three individuals participated, including 6 bereaved parents, 8 photographers, and 9 health care professionals. Analyses generated 5 major themes describing ways in which the photographs were valuable to parents: validation of the experience, permission to share, creation of a permanent and tangible legacy, creation of positive memories, and moving forward after the loss. Hospitals should consider incorporation of professional bereavement photography services into palliative care and bereavement programs.